ESG, Financial Performance, and the Moderating Role of ESG Controversies - Suci Rahmadini; Dwi Hartanti (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study aims to examine the relationship between Environmental, Social, and Governance (ESG) performance and financial performance (FP) and examine the relationship between ESG Controversies (ESGC) and FP, either directly or through moderation roles. Methods: This study used a quantitative approach with random effect panel data regression and secondary data obtained from Refinitive-Datastream. The sample in this study was 175 observations of non-financial sector companies on the IDX during 2019-2023. Findings: The study showed that ESG performance had a significant positive relationship with Tobin’s Q. However, subsequent findings found that ESGC had no significant relationship with FP, directly or through interactions with Tobin’s Q. Novelty: This study provides new insights by filling in the gaps in previous research that examined the direct relationship between ESG, ESGC, and FP. This study will consider how the moderation role of ESGC or negative issues can affect the relationship in the context of the Indonesian market. However, with the limited sample covering Indonesia, the study results are difficult to generalize globally. Further, this study suggests expanding the sample to other sectors or companies in other countries to improve generalizations.